Off to a bad start: youth nonemployment and labor market outcomes later in life - Mattia Filomena; Isabella Giorgetti; Matteo Picchio (Empirical Economics, 2025)
We estimate the effect of nonemployment experienced by Italian youth after secondary school exit on subsequent labor market outcomes. We focus on the impact on earnings and labor market participation both in the short term and in the long term. By estimating a factor-analytic model that controls for time-varying unobserved heterogeneity, we find that the negative effect of nonemployment on earnings is persistent, being sizeable and statistically significant up to 25 years after school completion. Penalties in terms of participation last instead shorter. Hence, early nonemployment operates by persistently locking the youth who get off to a bad start into low-wage jobs.
Keywords: J01; J08; J31; J64; 330; Youth nonemployment; Scarring effects; Earnings; Labor market participation; Factor analytic model